How Critical is "Second Nature"? A Diagnosis and an Antidote - Louis Carré (Krisis, 2023)
The prior issue of Krisis (42:1) published Critical Naturalism: A Manifesto, with the aim to instigate a debate of the issues raised in this manifesto – the necessary re-thinking of the role (and the concept) of nature in critical theory in relation to questions of ecology, health, and inequality. Since Krisis considers itself a place for philosophical debates that take contemporary struggles as starting point, it issued an open call and solicited responses to the manifesto. This is one of the sixteen selected responses, which augment, specify, or question the assumptions and arguments of the manifesto.